Critical thinking and young children's exploration of picturebook artwork. (4th March 2017) - Pantaleo, Sylvia
ABSTRACT: The data featured in this article were gathered during a classroom-based research project with Grade 2 (six- and seven-year-old) children. The overall purposes of the study included exploration of how the development of young children's understanding of elements of visual art and design would affect their comprehension, interpretation, and analysis of the artwork in a selection of picturebooks, as well as the subsequent application of the same elements when they created their own multimodal print texts. A discussion of critical thinking is followed by descriptions of the study's guiding theoretical and conceptual frameworks, as well as an overview of relevant literature, the research context and methods, and the data analysis procedures. The findings from the content analysis of the students' written responses about the artwork of one picturebook are discussed with reference to key concepts associated with critical thinking. The conclusion features a consideration of how students' critical thinking skills and esthetic development can be enhanced by instruction about elements of visual art and design in picturebooks.